Effect of Iron Toxicity on the Growth of Calliandra calothyrsus and Leucaena leucocephala Seedlings - Mohammad Agus Salim; Luluk Setyaningsih; Imam Wahyudi; Sri Wilarso Budi R (Universitas Gadjah Mada, 2021)
Iron (Fe) is a micro essential needed by plants in small amounts and can be toxic when available in large quantities. This study aimed to evaluate how Fe exposure affects the growth of C. callothyrsus and L. leucocephala seedlings. This study used a completely randomized design with factorial, where the first factor consisted of two levels of seedlings (C. calothyrsus and L. leucocephala), and the second factor consisted of Fe concentration which consisted of 8 levels (0, 0.25, 0.5, 0.75, 1, 1.25, 1.5, and 1.75 mM). The results showed that treatment of seedlings species and concentration of Fe was able to significantly affect the growth parameters (height, root length, root dry weight, shoots, and plant dry weight) of seedlings. The control treatment (without Fe) showed the highest growth response compared to those treated with Fe exposure and an increase in Fe concentration was able to reduce all growth parameters in both seedlings. The 0.5 mM Fe concentration reduced all growth parameters of C. calothyrsus drastically, while in L. leucocephala, the Fe 0.75 concentration was able to decrease all growth parameters drastically. The tolerance index of both seedlings decreased with increasing Fe concentration. The rate of photosynthesis did not show a significant difference between treatments, meanwhile, it had a significant effect on chlorophyll affect chlorophyll (a, b, and total chlorophyll) and carotenoid content. The highest Fe content in C. calothyrsus seedlings was at a concentration of 1.5 mM (4.40%), while in L. leucocephala seedlings, the highest Fe content was at 1.7 mM (2.87%).